2017
DOI: 10.1007/s10393-017-1252-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Bushmeat Hunger in the Congo Basin

Abstract: Unlike the Sudano-sahelian regions, which are confronted to severe periods of food shortage, tropical rainforests are known to provide a constant supply of a great diversity of food resources that mitigates the risk of food starvation for omnivorous humans. Nevertheless, several African forest ethnic groups suffer from a seasonal hunger induced by depletion in the procurement of bushmeat, which is a food of paramount importance. Although the diet remains well balanced and meets all the nutritional needs, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Active promotion of local husbandry efforts to raise food animals is one way this could be accomplished. It must be noted, however, that changing people’s behaviors and food preferences have often proven to be challenging [66]. Consumption of ‘bush meat’ among urbanized populations, for example, is often driven by cultural preference rather than need.…”
Section: One Health and Intersectoral Responses During Monkeypox Outbmentioning
confidence: 99%
“…Active promotion of local husbandry efforts to raise food animals is one way this could be accomplished. It must be noted, however, that changing people’s behaviors and food preferences have often proven to be challenging [66]. Consumption of ‘bush meat’ among urbanized populations, for example, is often driven by cultural preference rather than need.…”
Section: One Health and Intersectoral Responses During Monkeypox Outbmentioning
confidence: 99%
“…Recent studies reported that among the Baka, a foragerhorticulturalist group from the Congo Basin, the level of sedentarization and market integration influences their dietary diversity (Reyes-García et al 2019) and health (Dounias and Froment 2006). In this tropical region, while wild meat is the main protein source (Cawthorn and Hoffman 2015), and access to meat is closely tied with health and wellbeing (Dounias and Ichikawa 2017;Vliet et al 2017), the increased demand for bushmeat in towns, the traffic of ivory, and the introduction of more efficient hunting practices have led to a bushmeat crisis (Duda 2017;Ichikawa and Kimura 2003). These changes have affected the way local populations use and perceive animals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Yambe are making roughly as much as a 550% profit on the exchange, with little if any cash proceeds returning to BaYaka. Importantly, however, meat is a highly desired food that is widely shared among Congo Basin foragers and has important nutritional value (Bahuchet, 1990;Dounias & Ichikawa, 2017;Kitanishi, 1998). Hunters' wives and families complain if men bring meat into camp that will not be shared but given to the gun owner (Lewis, 2005;Riddell, 2013).…”
Section: Discussionmentioning
confidence: 99%